Digital Marketing Strategies by Start-Ups in a VUCA Context - Joshi, Manoj; Enwereji, Prince Chukwuneme; Nwosu, Lilian Ifunanya (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
In the volatile, uncertain, complex, and ambiguous (VUCA) business environment of today, online marketing has become crucial for connecting with customers and the community. Organisations leverage online marketing to retain and grow their customer base by fostering engagement and building strong community ties. This study explores how start-up leaders utilise online marketing systems to achieve these benefits. Targeting successful small retail business owners in India, the research involved semi-structured and face-to-face interviews, while other data sources include reviews of public documents, company websites, and social media sites. The findings reveal the strategies that start-ups use to boost sales through digital marketing. Four key themes emerged from data collection and analysis: (a) social media platforms and strategies; (b) online marketing strategies and challenges; (c) online content strategies; and (d) follow-up strategies. These findings expounded upon the digital marketing techniques employed by business organisers to increase sales, build strong customer relationships, and promote community development. The study recommended that start-ups should enhance the use of social media platforms, refining online content to better engage target audiences, address the challenges inherent in online marketing, and develop robust follow-up strategies to maintain customer relationships. The study highlights how these businesses would enhance brand recognition, drive progress, and maintain sustainability by utilising various communication networks to advance and promote products and services in the retail industry.